Source analysis and health risk assessment of polycyclic aromatic hydrocarbon (PAHs) in total suspended particulate matter (TSP) from Bengbu, China - Danchen Wu; Liu Chen; Zhijing Ma; Dalin Zhou; Le Fu; Mengmeng Liu; Tianer Zhang; Jing Yang; Quan Zhen (Scientific Reports, 2024)
Abstract The polycyclic aromatic hydrocarbon (PAH) concentrations in total suspended particulate matter (TSP) samples collected from October, 2021 to September, 2022 were analyzed to clarify the pollution characteristics and sources of 16 PAHs in the atmospheric TSP in Bengbu City. The ρ(PAHs) concentrations ranged from 1.71 to 43.85 ng/m3 and higher concentrations were detected in winter, followed by spring, autumn, and summer. The positive matrix factorization analysis revealed that, in spring and summer, PAH pollution was caused mainly by industrial emissions, gasoline and diesel fuel combustion, whereas in autumn and winter, it was coal, biomass and natural gas combustion. The cluster and potential source factor analyses showed that long-range transport was a significant factor. During spring, autumn, and winter, the northern and northwestern regions had a significant impact, whereas the coastal area south of Bengbu had the greatest influence in summer. The health risk assessment revealed that the annual total carcinogenic equivalent concentration values for PAHs varied from 0.0159 to 7.437 ng/m3, which was classified as moderate. Furthermore, the annual incremental lifetime cancer risk values ranged from 1.431 × 10−4 to 3.671 × 10−3 for adults and from 6.823 × 10−5 to 1.749 × 10−3 for children, which were higher than the standard.